Absorption and excretion of elderberry (Sambucus nigra L.) anthocyanins in healthy humans - Frank, T; Janssen, M; Netzet, G; Christian, B; Bitsch, I; Netzel, M (Methods and findings in experimental and clinical pharmacology, 2007)
Pharmacokinetic variables of several dietary anthocyanins (potent natural antioxidants) following consumption of elderberry (Sambucus nigra L.) extract were evaluated in urine and plasma of six healthy volunteers. They were given a single oral dose of either 30 ml (278 mg total anthocyanins) or 200 ml (1852 mg total anthocyanins) of a commercially available elderberry extract. Within 7 h, the fraction of orally administered total anthocyanins (calculated as the sum of cyanidin-3-sambubioside and cyanidin-3-glucoside) excreted unchanged was 0.39% and 0.27% following ingestion of 30 and 200 ml, respectively. The elimination half-life of total anthocyanins was slightly lower following the consumption of 278 mg (1.85 h) than that after the consumption of 1852 mg (2.57 h). The renal clearance (median) of total anthocyanins was 196 and 169 ml/min, respectively. The peak and average systemic exposure to the major elderberry anthocyanidin glycosides in plasma as well as their renal excretion exhibited approximate dose-proportional characteristics within the administered range. The low dose-normalized area under the concentration-time curve (AUC) and the fraction of orally administered anthocyanins recovered unchanged in urine indicate a low bioavailability of these compounds.